Behaviour of Arctic charr Salvelinus alpinus during an induced mating season in captivity: how male relative size influences male behavioural investment and female preference over time. Issue 4 (20th December 2016) - Bolgan, M.; O'Brien, J.; Picciulin, M.; Manning, L.; Gammell, M.
Abstract : The behaviour of sexually mature Arctic charr Salvelinus alpinus specimens (fifth farm generation) was observed in captivity for four consecutive days. Only agonistic interactions between males of different size were facilitated on the first 2 days, while both agonistic and courtship interactions were possible from the third day up to the end of the experiment. The reliability of behavioural analysis was assessed in order to reduce the possibility of observer errors within the generated datasets. The behavioural investment of big males, small males and females was analysed using general linear models (two‐way repeated measures ANOVAs with time and male size as factors). A peak in the agonistic interactions between males occurred during the first day of interactions, where the agonistic investment of big males was significantly higher than that of small males. This resulted in an increased investment in submissive behaviour by the small males, who consistently performed submissive behaviours from the second day of interactions up to the end of the trial. Big males were found to invest significantly more than small males in courtship behaviours for the duration of the trial. Even though females performed inter‐sexual behaviours towards both big and small males for the entire observation period, female interaction rate towards big males was higher than towards small males. This study suggests that both male investment in mating behaviour and female preference might be related to male characteristics such as body length and that S. alpinus behavioural patterns and mate choice cues might be strongly context‐related and characterized by high levels of behavioural plasticity ( i.e. presence–absence of certain behavioural units or potential reversal of a mate choice cue) within the same species. Finally, in light of this, some conservation measures are discussed. In particular, effective management plans should take into account the high level of behavioural plasticity likely to be occurring in this species.